Epidemiology of hypertension and examination of hypertensive patient - Lewandowski, Jacek (Przewodnik Lekarza/Guide for GPs, 2010)
Hypertension is one of the most prevalent risk factors of cardiovascular diseases. It is estimated that in industrialized countries hypertension affects more than 25% of adults. In Poland hypertension is diagnosed in 29% of adults, while only 12% of patients is treated effectively. Since hypertension increases cardiovascular risk it should be promptly diagnosed and appropriately treated. Data concerning presence of risk factors, end-organ damage and coexisting diseases must be obtained during history taking. During physical examinations typical signs of end organ damage and coexisting cardiovascular diseases should be evaluated. Special emphasis should be placed on appropriate blood pressure measurement.